Local and Systemic IKKε and NF-κB Signaling Associated with Sjögren’s Syndrome Immunopathogenesis - Weiqian Chen; Jin Lin; Heng Cao; Danyi Xu; Bei Xu; Liqin Xu; Lihuan Yue; Chuanyin Sun; Guolin Wu; Wenbin Qian (Journal of Immunology Research)
The activated NF-κB signaling pathway plays an important role in pathogenesis of primary Sjögren’s syndrome (pSS). The inhibitor of κB (IκB) kinase (IKK) family such as IKKα, IKKβ, IKKγ, and IKKε, is required for this signaling. Our aim was to investigate the role of IKKα/β/γ/ε in patients with untreated pSS. In minor salivary glands from pSS patients, phosphorylated IKKε (pIKKε), pIκBα, and pNF-κB p65 (p-p65) were highly expressed in ductal epithelium and infiltrating mononuclear cells by immunohistochemistry, compared to healthy individuals. pIKKα/β and pIKKγ were both negative. And pIKKε positively related to expression of p-p65. Furthermore, pIKKε and p-p65 expression significantly correlated with biopsy focus score and overall disease activity. Meanwhile, in peripheral blood mononuclear cells from pSS patients, pIKKε, total IKKε, pIKKα/β, and p-p65 were significantly increased by western blot, compared to healthy controls. However, there was no difference in IKKγ and IκBα between pSS patients and healthy individuals. These results demonstrated an abnormality of IKKε, IκBα, and NF-κB in pSS, suggesting a potential target of treatment for pSS based on the downregulation of IKKε expression and deregulation of NF-κB pathway.